2018
DOI: 10.1002/ajpa.23423
|View full text |Cite
|
Sign up to set email alerts
|

Archaeogenetics of Late Iron Age Çemialo Sırtı, Batman: Investigating maternal genetic continuity in north Mesopotamia since the Neolithic

Abstract: Despite the region's complex sociopolitical history and indication for increased genetic diversity over time, we find no evidence for sharp shifts in north Mesopotamian maternal genetic composition within the last 10,000 years.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…In addition, some sequenced individuals identifying as Kodava, Kodava_US and Nair belong to subclades of macro-haplogroup HV, a major subclade of haplogroup R0 (Shamoon-Pour, Li, and Merriwether 2019). We observe subclades of this haplogroup that have been reported in ancient and present-day individuals from South Asia, Central Asia, the Middle East, West Asia, central and eastern Europe, and the Caucasus (Narasimhan et al 2019; Derenko et al 2013; Shamoon-Pour, Li, and Merriwether 2019; Al-Zahery et al 2003; Yaka et al 2018; Mathieson et al 2018). One individual identifying as Kodava_US is assigned to haplogroup A1a, a subclade of haplogroup A primarily observed in East Asia (Tanaka et al 2004) that has, to our knowledge, not been reported in Indian populations.…”
Section: Resultssupporting
confidence: 66%
“…In addition, some sequenced individuals identifying as Kodava, Kodava_US and Nair belong to subclades of macro-haplogroup HV, a major subclade of haplogroup R0 (Shamoon-Pour, Li, and Merriwether 2019). We observe subclades of this haplogroup that have been reported in ancient and present-day individuals from South Asia, Central Asia, the Middle East, West Asia, central and eastern Europe, and the Caucasus (Narasimhan et al 2019; Derenko et al 2013; Shamoon-Pour, Li, and Merriwether 2019; Al-Zahery et al 2003; Yaka et al 2018; Mathieson et al 2018). One individual identifying as Kodava_US is assigned to haplogroup A1a, a subclade of haplogroup A primarily observed in East Asia (Tanaka et al 2004) that has, to our knowledge, not been reported in Indian populations.…”
Section: Resultssupporting
confidence: 66%
“…Reports from Turkey vary greatly (4–24%), but combining 490 samples from five studies puts the average frequency of HV*(xH,V) at 5.1% 14,1619 . MtDNA data from the ancient Near East is limited, however, aDNA studies have revealed the presence of HV*(xH,V) lineages in Iran (HV), Levant (HV*, HV1b2), southeast Anatolia (HV*, HV8) and South Caucasus (HV*, HV1a, HV12) 15,2023 . The oldest cases of HV*(xH,V) reported so far are from Tell Halula in Syria (>9 kya) 21 , and Ganj Dareh in Western Iran (8.8 kya) 22 , with the latter individual being the only representative of the ancestral node of HV haplogroup.…”
Section: Introductionmentioning
confidence: 99%
“…Although this analysis is compromised by the partly arbitrary nature of haplogroups, it does imply the relative stability of the maternal gene pool, consistent with earlier work in various regions. 27 , 28 , 29 It would also be compatible with stronger genetic drift in the male gene pool and/or higher rates of male mobility, with the most notable effect in the Levant (Figures XXI–XXIII in Document Z1).
Figure 6 Uniparental markers and sex-biased admixture (A) Distribution of mtDNA and Y chromosome haplogroups among time periods across all regions of Southwest Asia and the East Mediterranean.
…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we tackle the question of possible sex bias in human mobility, given earlier suggestions of long-term matrilineal continuity in the region. 27 , 28 , 29 …”
Section: Introductionmentioning
confidence: 99%